Propensity of self-assembled leucine-lysine diblock copolymeric alpha-helical peptides to remain in parallel and antiparallel alignments in water - Sarkar, Sujit; Pandey, Prithvi Raj; Roy, Sudip (Journal of Physical Chemistry B, 2015)
Molecular dynamics Simulation study of alpha-helical diblock copolypeptides: preassembled in parallel and antiparallel alignments in water are presented. The assembled peptide lamellar structures were not disrupted even: after performing three step simulation protocols. Primarily hydrogen bonds between peptide are responsible for the stability: The analysis of the trajectory also suggests that Water plays a significant role in favoring self assembly We have detected continuous hydrogen bonded network structure, which is further responsible for the stability Of the lamellar structures. We have performed a detailed analysis of the hydrogen bonded network structure and its length. Further, free energy calculations revealed that the degree of stability for both lamellae are similar. The present study provides structural insight into the stability of self-assembled structures of block copolypeptides.

Proton transport mechanism of imidazole, triazole and phosphoric acid mixtures from ab initio molecular dynamics simulations - Pahari, Swagata; Roy, Sudip (Physical Chemistry Chemical Physics, 2015)
We performed first principles molecular dynamics simulations to elucidate the mechanism and role of 1,2,3-triazole in proton transport while it is mixed with phosphoric acid (PA) and a phosphoric acid imidazole mixture. PA doped imidazole based polymer acts as an efficient polyelectrolyte membrane for fuel cells. The conductivity of this membrane increases when triazole is added to the system. For the first time we performed ab initio molecular dynamics simulations of complex mixtures of PA, imidazole and triazole. We have quantitatively estimated the structural diffusion and vehicular motion of protons. We found that upon the addition of triazole in PA and the PA imidazole mixture, the structural diffusion of protons increases significantly. The mechanism of proton transport is different when triazole is added to the mixture. We have also identified two different paths for structural diffusion (constructive and non-constructive) that contribute to long and short range proton transport.

Probing the ATP-induced conformational flexibility of the PcrA helicase protein using molecular dynamics simulation - Mhashal, Anil R.; Choudhury, Chandan Kumar; Roy, Sudip (Journal of Molecular Modeling, 2016)
Helicases are enzymes that unwind double-stranded DNA (dsDNA) into its single-stranded components. It is important to understand the binding and unbinding of ATP from the active sites of helicases, as this knowledge can be used to elucidate the functionality of helicases during the unwinding of dsDNA. In this work, we investigated the unbinding of ATP and its effect on the active-site residues of the helicase PcrA using molecular dynamic simulations. To mimic the unbinding process of ATP from the active site of the helicase, we simulated the application of an external force that pulls ATP from the active site and computed the free-energy change during this process. We estimated an energy cost of similar to 85 kJ/mol for the transformation of the helicase from the ATP-bound state (1QHH) to the ATP-free state (1PJR). Unbinding led to conformational changes in the residues of the protein at the active site. Some of the residues at the ATP-binding site were significantly reoriented when the ATP was pulled. We observed a clear competition between reorientation of the residues and energy stabilization by hydrogen bonds between the ATP and active-site residues. We also checked the flexibility of the PcrA protein using a principal component analysis of domain motion. We found that the ATP-free state of the helicase is more flexible than the ATP-bound state.
Keywords: ATP; DNA helicase; PcrA; Residue reorientation; Translocation; Umbrella sampling; Unwinding

Phase diagram of self-assembled sophorolipid morphologies from mesoscale simulations - Sarkar, Sujit; Chakraborty, Souvik; Roy, Sudip (Journal of Molecular Liquids, 2018)
We have constructed a phase diagram from the self-assembled morphologies of linolenic acid sophorolipid in water by performing mesoscale simulations in different concentrations. The dependence of morphologies and its properties of the self-assembled structure as a function of the concentration of bolaamphiphile in water are investigated. Two hydrophilic head groups and one hydrophobic tail group of bolaamphiphile have been mapped to beads for mesoscale simulation. The interaction parameters between different beads are calculated using Flory-Huggins solution theory. Flory-Huggins x-parameters have been calculated from atomistic simulation and experimental data of pure components constituting linolenic acid sophorolipid. We have obtained different self-assembled morphologies depending upon the concentrations of sophorolipid in water. We have explored the arrangements of hydrophobic and hydrophilic groups of the sophorolipid chains in the different morphologies. The sophorolipid chains found to be present in different structural arrangements. The residence time and flip frequency of these lipids in different orientations have been calculated and discussed in this work. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Bolaamphiphile; Flip frequency; Mesoscale simulation; Orientation of chains; Self-assembly